2008
DOI: 10.1007/s10238-008-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIF-1α on human gastric cancer cell apoptosis at different CO2 pressures

Abstract: The effects and potential molecular mechanisms underlying carbon dioxide (CO(2)) pneumoperitoneum on gastric cancer cell apoptosis are not fully understood. In this study, we assessed the effects of CO(2) pneumoperitoneum on the apoptosis of MKN-45 gastric cancer cells. Additionally, we investigated the role of HIF-1alpha in CO(2) pneumoperitoneum-induced apoptosis of gastric cancer cells. MKN-45 cells were cultured in CO(2) or air pneumoperitoneum at 0, 12 and 15 mmHg pressures for 4 h. We observed a change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Hao et al . reported that exposure of gastric cancer cells to CO 2 pneumoperitoneum significantly induced apoptosis [26]. In the current study, we demonstrate that transcutaneous application of CO 2 to human MFH cells in an engrafted tumor model, upregulated the expression of PGC-1α and TFAM, increased the number of mitochondria, and led to mitochondrial-induced apoptosis.…”
Section: Discussionsupporting
confidence: 66%
“…Hao et al . reported that exposure of gastric cancer cells to CO 2 pneumoperitoneum significantly induced apoptosis [26]. In the current study, we demonstrate that transcutaneous application of CO 2 to human MFH cells in an engrafted tumor model, upregulated the expression of PGC-1α and TFAM, increased the number of mitochondria, and led to mitochondrial-induced apoptosis.…”
Section: Discussionsupporting
confidence: 66%
“…[41] Basic research in vitro also demonstrated that CO 2 pneumoperitoneum did not increase the proliferation rate and invading ability of gastric cancer cells. [42,43] …”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 and Bax both are members of Bcl-2 family. The former is an anti-apoptosis protein and the latter is a pro-apoptosis protein (20). In the present study, overexpression of GSTM3 downregulated the Bcl-2 expression and upregulated the Bax expression.…”
Section: Discussionmentioning
confidence: 99%